Phytochemical and bioactivity studies on amphilophium paniculatum ( L. ) kunth and markhamia lutea ( Benth ) : Family bignoniaceae - Dina Mahfouz Eskander; Elsayed Ali Aboutabl; Mohmoud Ibrahim Ali Nassar (Cairo : Dina Mahfouz Eskander, 2013)
This work includes phytochemical and bioactivity studies on Amphilophium paniculatum and Markhamia lutea , family Bignoniaceae . Studying the following : literature surey of phyto constituents and bioactivities of certain Bignoniaceae species , DNA fingerprinting , investigation of volatile oil , investigation of lipoidal content , quantitative estimation of phenolic acids and flavonoids of the leaves of both plants and isolation , characterization and structure elucidation of the main constituents in n - butanol extract of Amphilophium paniculatum leaves
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacognosy
Issued also as CD
Keywords: Amphilophium paniculatum; Bioactivities; Markhamia lutea